Ethics of Language Through Speech Actions - Linda Handayani (Pusdikra-Publishing.com, 2023)
To engage in civilized discourse, three aspects need to be upheld: linguistic politeness, conversational politeness, and ethical discourse. Linguistic politeness involves the selection of respectful lexical elements and varied sentence structures; conversational politeness pertains to the social status of the interlocutor; and ethical discourse relates to the behavior while communicating. These three elements constitute a unity aimed at achieving the attribute of civilized discourse. Moreover, the ethical dimension of speaking, as discussed by Masinambouw and Geertz, emphasizes the connection between language use and societal norms. The ethics of speaking encompass considerations of appropriate speech topics, linguistic variety, turn-taking, active listening, vocal modulation, and physical demeanor. These ethical guidelines serve as a framework for individuals to communicate responsibly, demonstrate respect for social norms, and contribute to the harmonious functioning of society. In essence, effective communication encompasses not only the exchange of information but also the application of linguistic politeness and adherence to ethical discourse principles. As individuals navigate complex social contexts, understanding and employing these principles can facilitate meaningful and respectful interactions, fostering an environment of understanding, cooperation, and mutual respect.